Trends in Prescription Medication Use Among Children and Adolescents—United States, 1999-2014 - Hales, Craig M. (JAMA, 2018)
IMPORTANCE: Access to appropriate prescription medications, use of inappropriate or ineffective treatments, and adverse drug events are public health concerns among US children and adolescents. OBJECTIVE: To evaluate trends in use of prescription medications among US children and adolescents. DESIGN, SETTING, AND PARTICIPANTS: US children and adolescents aged 0 to 19 years in the 1999-2014 National Health and Nutrition Examination Survey (NHANES)—serial cross-sectional, nationally representative surveys of the civilian noninstitutionalized population. EXPOSURES: Sex, age, race and Hispanic origin, household income and education, insurance status, current health status. MAIN OUTCOMES AND MEASURES: Use of any prescription medications or 2 or more prescription medications taken in the past 30 days; use of medications by therapeutic class; trends in medication use across 4-year periods from 1999-2002 to 2011-2014. Data were collected though in-home interview and direct observation of the prescription container. RESULTS: Data on prescription medication use were available for 38 277 children and adolescents (mean age, 10 years; 49% girls). Overall, use of any prescription medication in the past 30 days decreased from 24.6% (95% CI, 22.6% to 26.6%) in 1999-2002 to 21.9% (95% CI, 20.3% to 23.6%) in 2011-2014 (β = −0.41 percentage points every 2 years [95% CI, −0.79 to −0.03]; P = .04), but there was no linear trend in the use of 2 or more prescription medications (8.5% [95% CI, 7.6% to 9.4%] in 2011-2014). In 2011-2014, the most commonly used medication classes were asthma medications (6.1% [95% CI, 5.4% to 6.8%]), antibiotics (4.5% [95% CI, 3.7% to 5.5%]), attention-deficit/hyperactivity disorder (ADHD) medications (3.5% [95% CI, 2.9% to 4.2%]), topical agents (eg, dermatologic agents, nasal steroids) (3.5% [95% CI, 3.0% to 4.1%]), and antihistamines (2.0% [95% CI, 1.7% to 2.5%]). There were significant linear trends in 14 of 39 therapeutic classes or subclasses, or in individual medications, with 8 showing increases, including asthma and ADHD medications and contraceptives, and 6 showing decreases, including antibiotics, antihistamines, and upper respiratory combination medications. CONCLUSIONS AND RELEVANCE: In this study of US children and adolescents based on a nationally representative survey, estimates of prescription medication use showed an overall decrease in use of any medication from 1999-2014. The prevalence of asthma medication, ADHD medication, and contraceptive use increased among certain age groups, whereas use of antibiotics, antihistamines, and upper respiratory combination medications decreased.